2008
DOI: 10.1002/app.27998
|View full text |Cite
|
Sign up to set email alerts
|

Grafted CMC/silica gel superabsorbent composite: Synthesis and investigation of swelling behavior in various media

Abstract: In the present study, we attempt to synthesize and characterize novel CMC-g-poly (acrylic acid-co-2-acrylamido-2-methylpropanesulfonic acid)/silica gel composite. Infrared spectroscopy and TGA thermal analysis were carried out to confirm the chemical structure of the hydrogel. Moreover, morphology of the samples was examined by scanning electron microscopy. The effect of reaction variables affecting on water absorbency of the composite and swelling behavior in various solvents, salt, and pH solutions was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…There is an interesting parallel between the effects of spacers and the effects of certain very fine mineral products, which were mentioned earlier (Pourjavadi et al 2008;Zhang et al 2008b;2009;Wang et al , 2011aEl Salmawi and Ibrahim 2011). Such nano-minerals, if poorly adhered to the adjacent polymeric material, can be expected to allow the opening up of fluid-filled spaces within the hydrogel.…”
Section: Cross-link Lengthmentioning
confidence: 87%
See 4 more Smart Citations
“…There is an interesting parallel between the effects of spacers and the effects of certain very fine mineral products, which were mentioned earlier (Pourjavadi et al 2008;Zhang et al 2008b;2009;Wang et al , 2011aEl Salmawi and Ibrahim 2011). Such nano-minerals, if poorly adhered to the adjacent polymeric material, can be expected to allow the opening up of fluid-filled spaces within the hydrogel.…”
Section: Cross-link Lengthmentioning
confidence: 87%
“…Water absorbency values generally in the range of 40 to 1400 g/g have been reported in such studies, with the highest value reported by Pourjavadi et al (2008). Copolymers incorporating CMC have also been prepared with polyvinyl alcohol (El Salmawi 2007), hydroxyethyl cellulose (Oppermann 1995;Lionetto et al 2003;Sannino and Nicolais 2005;Demitri et al 2008;Dai and Kadla 2009), and with hydroxypropylethyl cellulose (Faroongwarng and Sukonrat 2008).…”
Section: Copolymers Of Cmc By Reaction With Monomersmentioning
confidence: 96%
See 3 more Smart Citations